Venous Thromboembolism in Elderly High-Risk Medical Patients: Time Course of Events and Influence of Risk Factors. (July 2013) - Hull, Russell D.; Merali, Tazmin; Mills, Allan; Stevenson, Abigail L.; Liang, Jane
Venous thromboembolism (VTE) causes significant morbidity and mortality in hospitalized medical populations; however, medical patients do not currently receive thromboprophylaxis beyond their hospital stay. We reviewed the real-life occurrence of VTE-related care for 100 days post-hospitalization in Calgary, Canada. Using medical visit records with a unique patient identifier number applied throughout the city's hospitals, 989 high-risk patients were selected for review. Almost three-quarters of the elderly patients received appropriate prophylaxis while in hospital, and only 2% received prophylaxis on discharge. Over the 100-day follow-up, 21% of the patients presented with clinically suspected VTE, of which 3.8% had confirmed VTE. Patients with multiple risk factors (≥3) had the highest frequency of confirmed VTE (≥6.1%). This study suggests that the actual rate of VTE-related follow-up care in patients post-hospitalization is high in the first 100 days, particularly among those who have multiple risk factors, warranting consideration of extended thromboprophylaxis in this population.